Approaches to Promoting Information and Communication Technology for Learning Management in the 21st Century of Schools in Bang Mun Nak Campus under the Phichit Secondary Educational Service Area Office - Pintu, Manaphong; Sittirach, Thanakit (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this research were to study problems, skills, and find approaches to promote information and communication technology skills for 21st century learning management in educational institutions within the Bang Mun Nak Educational Consortium under the Phichit Secondary Educational Service Area Office. The sample and data sources used in this research consisted of 162 participants including experts, school administrators, government teachers, and educational personnel from the 2024 academic year. The research instruments were questionnaires and interview forms. Data were analyzed by calculating percentage, frequency, mean, standard deviation, and content analysis. The research findings revealed that the problems and skills in using information and communication technology for 21st century learning management in educational institutions within the Bang Mun Nak Educational Consortium under the Phichit Secondary Educational Service Area Office were overall at the highest level. When considering each aspect in descending order of means, it was found that internet usage skills had the highest mean, followed by digital technology safety skills. Two aspects tied for the third highest mean: digital media creation program skills and online collaboration skills. The aspect with the lowest mean was computer usage skills.